ANSI C63.12-1999 : American National Standard for Electromagnetic Compatibility Limits--Recommended Practice (IEEE, 2000)
This recommended practice presents a rationale for developing limits and recommends sets of limits that are representative of current practice. These limits may be adjusted in particular applications as circumstances dictate.
Keywords: Electromagnetic compatibility.; Electromagnetic interference.